Carbon stocks in Daniellia oliveri agroforestry parklands in the Sudano ‐sahelian zone of Cameroon - Dangai Y (Elsevier, 2021)
As the rate of forest degradation continues to rise, agroforestry systems may serve as a way of conserving species and carbon sinks. The aim of the study was to assess the contribution of Daniellia oliveri agroforestry parklands to the mitigation of climate change via the estimation of carbon stock in the Sudanian-Sahelian zone of Cameroon. To achieve it, an ecological study was carried out. A total area of 144 ha has been established in Daniellia oliveri agroforestry parklands. To meet this objective, the diameter at breast height of trees in Daniellia oliveri parklands was measured with regard to their age. Thus, allometric equations and the ascending hierarchical classification were used for the assessment of carbon stock and determination of the typology of Daniellia oliveri agroforestry parklands in the study area. The results show that Daniellia oliveri agroforestry parklands harbor 61 species belonging to 48 genera and 45 families. The carbon stored in Daniellia oliveri agroforestry parklands differs according to their age. It varies from 85.44±11.11 tC/ha for 1–10 year in young parklands to 236.55±4.96 tC/ha for those ≥30 years old. Carbon sequestration potential fluctuates from 312.71±40.77 CO2eq/ha for young parklands (1–10 years) to 865.77±18.20 CO2eq/ha in old one (≥30 years). The typology of Daniellia oliveri agroforestry parklands indicates the existence of three categories of parklands among which; type 1, the most representative of the area (52.78%) and capable of generating significant income. This study greatly contributes to the understanding of the usefulness of Daniellia oliveri agroforestry parklands for carbon sequestration. Actions to strengthen the protection of the trees of this ecosystem must be considered to minimize its long-term degradation and so that it can be a more sustainable source of carbon sequestration.